Use of Social Time in Iraqi culture - Alwan, Fajir J (Al-Adab Journal, 2019)
Post-modern societies conceive time as ‘money’, where every minute counts, whilst pre-modern societies treat time more liberally; hours and days are utilized less effectively, with little achieved at its end. Method: A quantitative method of data collection has been used to compare two samples from different cultures, Results: A large divide was observed between the sample of a post-modern society at Leeds University when compared to that of a pre-modern society in the form of students at Baghdad University. Conclusion: At present a large difference is observed between the two sample groups P<.0001. This may seem to be an unbridgeable gap when the two societies are compared side by side. Societal change is required in Iraq that draws importance to the value of time, and this should occur as the process of industrialization and urbanization proceeds at an accelerated pace in the future